P-55 Acute liver failure in Peru: epidemiology and problematic of support and management - Padilla, P. Martin (2024)
Acute liver failure (ALF) is a severe clinical entity that requires a rapid diagnosis and for its proper management requires adequate intensive care support and the possibility of liver transplantation. This study aimed to show clinical epidemiological characteristics of ALF and the problematics of its management in Peru.